Aelia Capitolina - Jerusalem in the Roman period: in light of archaeological research - Weksler-Bdolah, Shlomit (Mnemosyne, 2019)
Intro -- ‎Contents -- ‎Preface -- ‎Figures and Tables -- ‎Abbreviations -- ‎Chapter 1. Introduction -- ‎Chronological and Historical Framework -- ‎History of Research -- ‎Sources of Information for the Investigation of Aelia Capitolina -- ‎The Historical Sources -- ‎The Archaeological Evidence -- ‎Chapter 2. The Camp of the Legion X Fretensis -- ‎The Camp's Fortifications and Related Structures -- ‎Structures, Roads and Installations inside the Camp -- ‎The Roman Dump on the Slopes of the Southwestern Hill -- ‎A Few Comments Relating to the Army in Aelia Capitolina -- ‎Possible Reasons for the Sparsity of Remains of the Roman Army Camp in Jerusalem -- ‎The Role of the Army in Aelia Capitolina -- ‎Stamp Impressions of the Legio X Fretensis on Roof Tiles, Bricks and Ceramic Pipes -- ‎Chapter 3. Aelia Capitolina -- ‎The Foundation of the Colony -- ‎The Urban Layout: The City Gates -- ‎Streets and Plazas -- ‎The Plaza inside Damascus Gate -- ‎The Western Cardo -- ‎The Municipal Forum in the City Center -- ‎An Ancient Street along Christian Quarter Street (HaNotsrim, Hâret en-Naşârâ) -- ‎The Eastern Cardo -- ‎The south Decumanus along David Street and the Street of the Chain -- ‎David Street -- ‎The Street of the Chain -- ‎The Northern Decumanus along the Route of the Via Dolorosa -- ‎The East Forum and the Ecce Homo Arch -- ‎Summary: The Urban Street System -- ‎The Buildings of Aelia Capitolina -- ‎Temples and Ritual Compounds -- ‎Public Buildings in the Southeast of the City -- ‎Private Dwellings -- ‎Chapter 4. Aelia Capitolina in the Fourth Century -- ‎The Expansion of the City's Limits -- ‎The Construction of a Wide-Circumference City Wall -- ‎The Identity of the Population -- ‎The Christianization of the Cityscape -- ‎Aelia/Hierosolyma in the Fourth Century: Summary and Conclusions -- ‎Chapter 5. Water Supply: Cisterns, Pools and Aqueducts.